Downregulation of Cyclin-D, Wnt3a, and C-Myc in prostate cancer by dose-dependent combination of concentrated marine minerals and curcumin - Syafika Alaydrus, Sriwidodo Sriwidodo, Ajeng Diantini, Riezki Amalia, Wahyuni Wahyuni, Ayu Wulandari (Journal of Applied Pharmaceutical Science, 2025)
Prostate cancer presents a significant global health challenge, often exhibiting resistance to chemotherapy drugs and causing severe side effects from conventional treatments. These side effects include toxicity to normal cells and mineral deficiencies, which can lead to complications such as acute diarrhea, electrolyte imbalances, and chemotherapy-induced peripheral neuropathy. Natural compounds like curcumin offer promising synergistic anticancer properties with relatively low toxicity and can reduce co-delivered drug resistance. Concurrently, concentrated marine mineral (CMM) solutions, rich in essential minerals, are being explored as adjunct therapies to mitigate chemotherapy-induced mineral deficiencies and potentially enhance curcumin’s efficacy and uptake. This study evaluates the comparative cytotoxic effects of curcumin, CMM, and their combination against DU145 prostate cancer cells and HEK293 normal kidney cells, using cisplatin as a benchmark. Curcumin and CMM demonstrate potent inhibition of DU145 cells, classifying them as highly active while showing reduced cytotoxicity towards HEK293 cells compared to cisplatin. Combining curcumin and CMM enhances cytotoxicity against prostate cancer cells while mitigating toxicity to normal cells. Moreover, the combined treatment effectively downregulates Cyclin-D1, Wnt3a, and C-Myc expression in prostate cancer cells, with optimal effects observed at a 5 ppm curcumin and 5 ppm CMM ratio. These results underscore the potential of curcumin and CMM as a synergistic therapeutic strategy for prostate cancer, offering enhanced efficacy and reduced side effects compared to conventional cisplatin chemotherapy.
Keywords: Dose-dependent chemotherapy, natural chemotherapy, selective anticancer agent